The leader of the future : new visions, strategies, and practices for the next era - 4 0 16; 1918- Hesselbein, Frances,;Goldsmith, Marshall,;Beckhard, Richard; 5 (San Francisco, California : Jossey-Bass Publishers, 1996)
Over thirty essays present ideas and predictions about leadership and how it will operate and be characterized in the future.
Includes index.
Adult.
Keywords: 2 -- 0; 6; Leadership.;Strategic planning. -- 20; 20; 2